2014
DOI: 10.1038/nature13374
|View full text |Cite
|
Sign up to set email alerts
|

BRCA2 prevents R-loop accumulation and associates with TREX-2 mRNA export factor PCID2

Abstract: Genome instability is central to ageing, cancer and other diseases. It is not only proteins involved in DNA replication or the DNA damage response (DDR) that are important for maintaining genome integrity: from yeast to higher eukaryotes, mutations in genes involved in pre-mRNA splicing and in the biogenesis and export of messenger ribonucleoprotein (mRNP) also induce DNA damage and genome instability. This instability is frequently mediated by R-loops formed by DNA-RNA hybrids and a displaced single-stranded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
490
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(545 citation statements)
references
References 33 publications
32
490
1
Order By: Relevance
“…2B and 3B). Moreover, other familial ALS proteins are involved in the prevention/repair of this type of damage (16,24), and BRCA1, which colocalizes with FUS and likely TDP43 at post-UV RNA Pol II DNA damage foci, also participates in the prevention and/or repair of R loop-associated DNA damage (18,26,27). Thus, we asked whether FUS and/or TDP43 participate in the prevention or repair of R loop-associated DNA damage by searching for a decrease in DNA damage following FUS or TDP43 depletion in cells that express ectopic RNASEH1.…”
Section: Depletion Of Fus and Tdp43 Leads To Excessive Transcription mentioning
confidence: 99%
“…2B and 3B). Moreover, other familial ALS proteins are involved in the prevention/repair of this type of damage (16,24), and BRCA1, which colocalizes with FUS and likely TDP43 at post-UV RNA Pol II DNA damage foci, also participates in the prevention and/or repair of R loop-associated DNA damage (18,26,27). Thus, we asked whether FUS and/or TDP43 participate in the prevention or repair of R loop-associated DNA damage by searching for a decrease in DNA damage following FUS or TDP43 depletion in cells that express ectopic RNASEH1.…”
Section: Depletion Of Fus and Tdp43 Leads To Excessive Transcription mentioning
confidence: 99%
“…In vitro, converging replisomes continue through their meeting point as one replisome displaces the other, resulting in over-replication, or a third copy, of the region where the forks meet (8). Complicating the process of genomic doubling even further, several studies have suggested that illegitimate initiations of replication frequently occur at single-strand nicks, gaps, Dloops, and R-loops throughout the genomes of both prokaryotes and eukaryotes (9)(10)(11)(12)(13)(14). Similar to when replication forks continue through a previously replicated template, each of these events would generate a third copy of the chromosomal region where the event occurs.…”
mentioning
confidence: 99%
“…Two regions upstream of the I-SceI cut site, P2 and P3, were examined. For each region, the relative enrichment of DNA-RNA hybrids was normalized to the signals obtained from input genomic DNA as well as the SNRPN negative-control region, as previously described for DRIP analysis (27)(28)(29). The average percent IPs in control (scrambled siRNA-transfected) cells for the SNRPN (negative control), P2, and P3 loci were 0.06%, 0.55%, and 2.42%, respectively.…”
mentioning
confidence: 99%
“…Twenty-four hours after DNA transfection, 4-hydroxytamoxifen (Sigma) was added to a final concentration of 5 M. Cells were incubated for 4 h and then harvested. The procedure for preparing nucleic acids for DNA-RNA immunoprecipitation (DRIP) analysis has been reported previously (27). Briefly, nucleic acids (genomic DNA along with RNA) were purified by lysing cell pellets in 1% SDS and digesting the lysates overnight with 300 g/ml proteinase K. Nucleic acids were extracted using a neutral-pH phenol-chloroform (1:1) mixture followed by ethanol precipitation.…”
mentioning
confidence: 99%